2014
DOI: 10.1371/journal.pone.0095855
|View full text |Cite
|
Sign up to set email alerts
|

Acute Liver Failure in Rats Activates Glutamine-Glutamate Cycle but Declines Antioxidant Enzymes to Induce Oxidative Stress in Cerebral Cortex and Cerebellum

Abstract: Background and PurposeLiver dysfunction led hyperammonemia (HA) causes a nervous system disorder; hepatic encephalopathy (HE). In the brain, ammonia induced glutamate-excitotoxicity and oxidative stress are considered to play important roles in the pathogenesis of HE. The brain ammonia metabolism and antioxidant enzymes constitute the main components of this mechanism; however, need to be defined in a suitable animal model. This study was aimed to examine this aspect in the rats with acute liver failure (ALF).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…GSH is a tripeptide that plays important roles in maintaining reducing equivalents in the cells facing oxidative challenges (Dickinson and Forman, 2002). In the present study, GSH was remarkably decreased by TAA both in liver (Al-Attar, 2012; Amin et al, 2012) and brain (Singh et al, 2014) of MHE rats. The increased production of reactive oxygen and nitrogen oxide species (ROS/RNOS) in the brain cells, in turn, is likely to amplify the neuronal derangements associated with HE pathogenesis (Haussinger and Gorg, 2010).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…GSH is a tripeptide that plays important roles in maintaining reducing equivalents in the cells facing oxidative challenges (Dickinson and Forman, 2002). In the present study, GSH was remarkably decreased by TAA both in liver (Al-Attar, 2012; Amin et al, 2012) and brain (Singh et al, 2014) of MHE rats. The increased production of reactive oxygen and nitrogen oxide species (ROS/RNOS) in the brain cells, in turn, is likely to amplify the neuronal derangements associated with HE pathogenesis (Haussinger and Gorg, 2010).…”
Section: Resultssupporting
confidence: 53%
“…at 100 mg/ kg (in saline solution) thrice weekly for six weeks to induce HE as reported earlier (Singh and Trigun, 2010;Singh et al, 2014) with modification, whereas alpha-lactalbumin (Lacprodan ® alpha -10 kindly supplied from Arla food amba, Denmark) was administered orally at 100 and 150 mg/kg (in distilled water prior to use) for two weeks after induction of HE by TAA, dose selection was according to previous studies of our team (Nada, 2009;Mansour et al, 2013;Eliwa et al, 2014;Mansour et al, 2015;Nada et al, 2015). Vitamin C (L (+)-ascorbic acid, Merck Co., Darmstadt, Germany) was administered orally at 500 mg/kg for two weeks after induction of HEby TAA.…”
Section: Treatment Protocolmentioning
confidence: 94%
“…As NH 4 Ac-mediated toxicity and mortality was evident not before 4 dpf, we hypothesized that developmental alterations establishing a genetic or metabolic cascade, which is sensitive to NH 4 + , are responsible for the observed differences. Since cerebral glutamine-glutamate cycle is known to play a pivotal pathophysiological role in hyperammonemic conditions in humans [ 22 ] and was shown to be activated in a rat model of acute liver failure [ 23 ], we investigated whether glutamine synthetase and glutaminase were involved in NH 4 Ac-induced mortality. In zebrafish, three paralogs of glutamine synthetases, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study showed that the MDA and PC contents were reduced in conjunction with increased levels of dietary lysine (up to a certain point), suggesting that intestinal lipid and protein damage are reduced by an optimal lysine concentration. In general, the protective ability of dietary lysine against oxidative damage may correlate with an increased antioxidant ability, which can be reflected by antioxidant enzymatic activities and non-enzymatic antioxidants [ 47 ]. In our study, an optimal dietary lysine concentration significantly increased the activities of CAT, SOD, GST, GPx, and GR, as well as the GSH level, suggesting that lysine possesses enzymatic and non-enzymatic antioxidant abilities in the intestine of fish.…”
Section: Discussionmentioning
confidence: 99%